Surgical treatment of hemorrhoidal disease and its complications - Valls, Alberto; Albo, Manuel; Puig, Roberto (Cirugía del Uruguay, 1973)
When integrating this Round Table we must limit our exposure to the concepts and resources managed in our experience, excluding the discussion of other criteria and tactics profusely exposed in the bibliography.